Jk(a−b−) phenotype screening by the urea lysis test in Thai blood donors - Deelert, Suparat (Edizioni SIMTI — SIMTI Servizi Srl, 2010)
BACKGROUND: The Jk(a−b−) phenotype is rare in most populations and often detected after transfusion or pregnancy. After immunisation, anti-Jk3 forms and it can be difficult to find compatible Jk(a−b−) donors. Using anti-Jk(a) and anti-Jk(b) in a conventional tube method is unsuitable for identifying Jk(a−b−) in mass screening of blood donors. Jk(a−b−) phenotypes are associated with the absence of urea transporters on erythrocytes, making red blood cells (RBC) resistant to lysis by 2M urea, while Jk(a+b−), Jk(a−b+) and Jk(a+b+) phenotypes are susceptible to lysis. MATERIALS AND METHODS. We screened for Jk(a−b−) phenotypes in blood donors by the urea lysis test using a 96-well microplate. The Jk(a−b−) phenotypes were confirmed by the indirect antiglobulin test (IAT). RESULTS: Altogether, 20,163 blood samples from Thai blood donors were tested and only RBC from five samples were resistant to lysis by 2M urea, while 20,158 samples were completely lysed within 5 min. In an IAT, both anti-Jk(a) and anti-Jk(b) failed to agglutinate RBC from all five samples. Using a micro-titre plate, the direct urea lysis test, costs • 0.01, about 480 times less than IAT. Moreover, the test time for each plate (94 samples) is about 18 times less than that for IAT. CONCLUSION: Jk(a−b−) phenotype screening by the direct urea lysis test on samples in a micro-titre plate is simple, cost-effective and practical for mass screening of blood donors.